2022
DOI: 10.3390/ijerph191912557
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Mental Health Service Use among Palestinian-Arab Women in Israel: Psychological Distress as Moderator

Abstract: Background: Many studies indicate that ethnic minority women, including women from the disadvantaged Palestinian-Arab minority in Israel, experience higher rates of psychological distress but are less likely to use mental health services. This study examined psychological distress and its role as a moderator in the relationship between mental health service use and stigma-related, attitudinal, and instrumental barriers. Method: Cross-sectional study of 146 Palestinian-Arab women who completed measures of psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Tese fndings are particularly important for groups with high negative attitudes towards mental disorders and their treatment, such as Arab societies [35], and for groups with low rates of mental health service use, such as various ethnic minorities [11]. Tey are consistent with recent studies showing that attitudes and perceptions in general are related to health outcomes and behaviors [36][37][38], and highlight the need for intervention programs to seriously consider improving attitudes and reducing stigma, alongside addressing barriers associated with minority service users' disadvantaged socioeconomic status.…”
Section: Discussionsupporting
confidence: 78%
“…Tese fndings are particularly important for groups with high negative attitudes towards mental disorders and their treatment, such as Arab societies [35], and for groups with low rates of mental health service use, such as various ethnic minorities [11]. Tey are consistent with recent studies showing that attitudes and perceptions in general are related to health outcomes and behaviors [36][37][38], and highlight the need for intervention programs to seriously consider improving attitudes and reducing stigma, alongside addressing barriers associated with minority service users' disadvantaged socioeconomic status.…”
Section: Discussionsupporting
confidence: 78%
“…Researchers have discovered that an individual’s stance regarding obtaining “formal mental health services” can significantly impact their choice to seek professional help when signs of mental health problems manifest (Derr, 2016 ; Ikonte et al, 2020 ; Khan et al, 2019 ). The relationship between an individual’s views and subsequent conduct can provide critical insights into cultural variation in help-seeking behaviors (Abo-Rass, et al, 2022 ; Bulut & Brewster, 2021 ).…”
Section: A Brief Background Of Arabs’ Mental Health Service Utilizationmentioning
confidence: 99%
“…Although earlier research has indicated inaccessibility to such care among Arab immigrants as a clinical issue (Abo-Rass, et al, 2022 ; Khan et al, 2019 ) this inaccessibility is not recognized as a social or policy concern. To focus public attention on this issue, it must be re-contextualized (Khan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%